Reimagining Digital Literacies from a Feminist Perspective in a Postcolonial Context - Maha Bali (Media and Communication, 2019)
Although there are many intersecting but also conflicting definitions and understandings of digital literacy, for the most part, the majority allude to critical thinking in some form or another. This article attempts to imagine a conception of digital literacy and practice of teaching digital literacy that considers a different approach to being critical while using digital technology to consume, produce and communicate. The approach builds on the feminist work of Belenky, Clinchy, Goldberger and Tarule’s (1986) Women's Ways of Knowing. The author will also share from her own teaching experience as a postcolonial scholar teaching Egyptian students at an American liberal arts university.